Inversores ZCZVT com acoplamento magnético: síntese e análise - Martins, Mário Lúcio da Silva (2008)
This Ph. D. Thesis presents a in deep study of the mechanism of resonant transition soft-switching techniques. By means of the principles that rules the PWM resonant transition converters, a novel tool for analysis and synthesis have been developed. This novel tool also permit to be verified some of the main factors that made possible to he ZVT technique to achieve its technology level. By means of this tool and with the definition of the basic requirements of the resonant transition converters a new concept concerning the ZCZVT technique have been generated, the ZCZVT converters with discontinuous auxiliary voltage source . The development of this new concept gives rise to a new family of ZCZVT converters with magnetically coupled auxiliary circuit. It also allowed a better perspective of the ZCZVT converters characteristics, advantages, drawbacks and limitations, which contributed significantly with the grown of the technology. Two of the six topologies with bi-directional auxiliary circuits proposed in the thesis have been mathematically analised. A design methodology based on constrains and dynamic characteristics of the IGBT and diode semiconductors under ZCS and ZVS conditions have been presented. Finally, experimental results proved the efficiency gain of the novel ZCZVT inverters with magnetically coupled auxiliary circuit. The ZCZVT inverter with magnetically coupled auxiliary circuit prototype have been compared with its Undeland snubber counterpart, presenting an efficiency of about 4% superior. It corroborates to the thesis proposal of developing novel topologies with better performance and simplicity.